PERENCANAAN TERMINAL PENUMPANG TIPE B UNTUK MENDUKUNG PENGEMBANGAN KAWASAN PUSAT PEMERINTAHAN KOTABARU PROVINSI LAMPUNG - Nafa Chairunnisa; Dessy Angga Afrianti; Syafek Jamhari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Kotabaru Area as the new governmental center of Lampung Province is projected to increase trip generation and attraction toward the area. However, Kotabaru Area currently does not have a transportation node in the form of a Type B Passenger Terminal to support integrated public transportation services. This study aims to determine the most suitable terminal location, plan terminal facility requirements based on public transport demand potential, and develop a terminal layout design. The research method used was descriptive qualitative and quantitative methods. Location analysis was carried out by comparing two alternative locations based on the technical criteria of Minister of Transportation Regulation Number 24 of 2021, including road performance, accessibility, conformity with spatial planning, route network suitability, land use, and regional development plans. Facility requirement analysis was conducted using weighting methods and queuing theory. The results show that Alternative Location II in Kotabaru Area is the most suitable location because it supports the development of the new governmental center, provides more optimal land development potential, and is supported by a good level of road service. Based on the analysis results, the terminal was planned using the minimum service standards for a Type B Passenger Terminal in accordance with Minister of Transportation Regulation Number 24 of 2021, with a layout design based on zoning systems and separated circulation between vehicles and passengers to minimize movement conflicts.